2017
DOI: 10.1097/shk.0000000000000897
|View full text |Cite
|
Sign up to set email alerts
|

Target Serum Sodium Levels During Intensive Care Unit Management of Aneurysmal Subarachnoid Hemorrhage

Abstract: In patients with SAH, both hyponatremia and hypernatremia during ICU management were significantly associated with unfavorable neurologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Referring to this summary, the optimal threshold seemed to be 145 mmol/L, as suggested in a previous study [ 60 ], and hypernatremia was associated with poor outcomes. The preventive effect of a specific drug or protocol on hypernatremia has not been tested to date.…”
Section: Reviewmentioning
confidence: 57%
See 3 more Smart Citations
“…Referring to this summary, the optimal threshold seemed to be 145 mmol/L, as suggested in a previous study [ 60 ], and hypernatremia was associated with poor outcomes. The preventive effect of a specific drug or protocol on hypernatremia has not been tested to date.…”
Section: Reviewmentioning
confidence: 57%
“…However, there are few studies describing the characteristics of sodium alteration in ICU. A single-center retrospective observational study showed that serum sodium concentrations increased for the first few days and decreased to the nadir level at 6–12 days [ 60 ]. A similar trend was observed in another retrospective study [ 61 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Починають із внутрішньовенного введення 1-2 літрів збалансованих сольових розчинів, а потім застосовують колоїди. При субарахноїдальних крововиливах рівень натрію сироватки плазми вищий 145 ммоль/л чи нижчий 132 ммоль/л веде до небажаних неврологічних наслідків у 88,2 % пацієнтів відділень інтенсивної терапії [21]. Рекомендують також раннє призначення флудрокортизону, особливо хворим із травматичним субрахноїдальним крововиливом [19].…”
Section: препаратunclassified